Leadership and Leading by Example Navigating The Shadow of Silent Bullying - Hadijah, Ahmad (UMPSA, 2023)
The issue of workplace bullying appears to be gaining traction in the public discourse. In this regard, higher education institutions are not an exception. A majority of those who have been subjected to bullying in academia have not reported the behaviour to their institutions for fear of retaliation. In the majority of cases, intimidation was condoned by a superior, such as the dean of the faculty, staff holding senior positions, or junior staff holding power positions.